2018
DOI: 10.1093/pch/pxy164
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refrigeration or freezing on human milk macronutrients and energy content in early lactation: Results from a tertiary centre survey

Abstract: Background: Neonates with severe conditions that cannot be breastfed should receive fresh or preserved expressed human milk in addition to parenteral nutrition. Objective: To identify the time during lactation when the macronutrients provide maximum energy and evaluate the effect of refrigeration and freezing. Methods: We analyzed the composition of fresh milk, refrigerated at +4°C and frozen at −20°C, expressed by mothers of 60 preterm and 30 term infants from a level III maternity, in colostrum, transitional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The decrease in milk constituents was attributed to coagulation and degradation when frozen milk is thawed. Specifically, the protein decrease was in agreement with a previous study by Păduraru et al (2019) on the influence of refrigeration or freezing on human milk macronutrients. Another study by Vieira et al (2011) reported up to 13.6% decrease in protein content when human milk was frozen and thawed.…”
Section: Discussionsupporting
confidence: 92%
“…The decrease in milk constituents was attributed to coagulation and degradation when frozen milk is thawed. Specifically, the protein decrease was in agreement with a previous study by Păduraru et al (2019) on the influence of refrigeration or freezing on human milk macronutrients. Another study by Vieira et al (2011) reported up to 13.6% decrease in protein content when human milk was frozen and thawed.…”
Section: Discussionsupporting
confidence: 92%
“…Buffalo milk is ideal for making butter, cream, and yoghurt because of its high protein and fat content, which gives it a rich and delicate texture. In particular, the trend towards lower protein concentration is consistent with a prior study on the effects of freezing or refrigeration on the macronutrients in human milk reported by Pȃduraru et al [33]. The decrease in protein has been attributed to several factors.…”
Section: Physicochemical Parameters and Milk Compositions Of Buffalo ...supporting
confidence: 91%
“…A summary of 44 articles 15 demonstrated that Holder pasteurization has the highest effect on the composition of bioactive components in human milk. Inconsistent findings from previous studies could be explained by the duration and temperature at which milk samples are stored before pasteurization, 16,17 method of thawing, 18 by the quantities of milk being pasteurized, by the choice of equipment for Holder pasteurization, 15,19 and finally by the method used to prepare the milk samples for testing. 20 Our study has demonstrated that the storage of frozen human milk at -40°C up to 10 months, followed by thawing and pasteurization, has no significant effect on macronutrient (protein, fat, and carbohydrate) or energy content of human milk.…”
Section: Discussionmentioning
confidence: 90%